Akebia Saponin D prevents axonal loss against TNF-induced optic nerve damage with autophagy modulation - Sase, Kana (Mol Biol Rep, 2020)
Akebia Saponin D (ASD), a triterpenoid saponin, was shown to have protective effects in certain neuronal cells. The purpose of the present study was to investigate the possibility of ASD to prevent tumor necrosis factor (TNF)-induced axonal loss and the ASD modulation of the biologic process of autophagy in optic nerves. Rats were given intravitreal administration of TNF, simultaneous administration of 2, 20, or 200 pmol ASD and TNF, or ASD alone. LC3-II and p62 expression, which is a marker of autophagic flux, and phosphorylated p38 (p-p38) expression in optic nerves were examined by immunoblot analysis. Morphometric analysis revealed a significant ameliorated effect of ASD against TNF-induced optic nerve damage. p62 was significantly increased in the optic nerve in TNF-treated eyes, but this increase was totally prevented by ASD. The ASD alone injection showed significant reduction of p62 levels compared with the PBS-treated control eyes. LC3-II was significantly increased by ASD treatment in the TNF-injected eyes. p-p38 was significantly increased in the optic nerve in TNF-treated eyes, but this increase was completely prevented by ASD. The protective effects of ASD may be associated with enhanced autophagy activation and inhibition of p-p38.